The Use of Google Form Application in the Implementation of the Final Semester Summative Assessment of Indonesian Subjects - Fahrul Rosadi, Ahmad; Lukmanul Hakiem, Fakhry; Suta Wardianto, Bayu; Hilaliyah, Tatu (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to analyze the effectiveness of using Google Form as a summative assessment tool in Indonesian subjects. This research was conducted on students at SMP Negeri 17 Serang City. The method used is qualitative with case studies. This approach was chosen in the study because it aims to describe and obtain an in-depth picture of the use of Google Forms in the implementation of summative assessments. The results of the study show that the use of Google Form increases student learning motivation, improves the quality of student learning outcomes, or makes it easier for teachers to manage assessment data. In conclusion, Google Form can be an effective alternative in the implementation of summative assessments in Indonesian subjects.